2005
DOI: 10.1111/j.1439-0531.2005.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Post‐ovulatory Insemination on the Subsequent Embryonic Loss, Oestrous Cycle Length and Vaginal Discharge in Sows

Abstract: The aim of present study was to study the effect of post-ovulatory insemination on the subsequent embryonic loss, oestrous cycle length and vaginal discharge in sows. Ten Large White multiparous sows were divided into two groups. Group A sows were inseminated once at 15 h after ovulation. Thereafter, they were ovariohysterectomized on day 11 (n = 5, first day of standing oestrus = day 1) and flushed for recovery of embryos. Group B sows were also inseminated once at 15 h after ovulation. They were further obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…It is recommended that a fertilization rate correlated positively when the insemination took place between 0 and 24 h before ovulation (Soede et al 1995;Steverink et al 1997). Late insemination caused a drop in FR (Rozeboom et al 1997;Kaeoket et al 2005). The reproductive performance obtained in the study was comparable to those obtained from our previous studies where AI was performed by our technicians (Am-in 2005;Am-in et al 2010) or the data in commercial farms as shown by Suriyasomboon et al (2006).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is recommended that a fertilization rate correlated positively when the insemination took place between 0 and 24 h before ovulation (Soede et al 1995;Steverink et al 1997). Late insemination caused a drop in FR (Rozeboom et al 1997;Kaeoket et al 2005). The reproductive performance obtained in the study was comparable to those obtained from our previous studies where AI was performed by our technicians (Am-in 2005;Am-in et al 2010) or the data in commercial farms as shown by Suriyasomboon et al (2006).…”
Section: Discussionsupporting
confidence: 82%
“…Because males and senior people in rural areas were mainly responsible for agriculture and farming (Jitapunkul et al 2001), they were more familiar with back pressure tests for heat detection and catheter insertion than others (Techakumphu et al 2008). Heat detection is the most important factor for successful AI because it marks the accurate period of insemination which affects sows' reproductive performance (Banbury 1965;Soede et al 1995;Kaeoket et al 2005). In our study, we found that heat detection is a major cause of failure of insemination and conception in the pigs of backyard farmers; more education on this subject is required.…”
Section: Discussionmentioning
confidence: 73%
“…Optimal fertility is reported with insemination occurring 12 hours before ovulation in competitive fertilization tests [104], and within 24 hours before ovulation with a single AI for fertilization rate and numbers of embryos [99], and farrowing rate and litter size [105,106]. Inseminations occurring too early or too late during estrus and in relation to ovulation can reduce fertility [92], and occurring too late in estrus can even increase embryo loss and cause endometritis [107].…”
Section: Estrus Detection and Inseminationmentioning
confidence: 99%
“…Sperm ejaculated from boars was collected by using the gloved-hand technique (Kaeoket et al , 2005(Kaeoket et al , 2010d. During collection, the semen was filtered through gauze, and only sperm-rich fractions were collected.…”
Section: Preparation Of Boar Spermatozoa Before Freezingmentioning
confidence: 99%